METODE PROBLEM BASED SOLVING PADA PEMBELAJARAN AKUNTANSI DI SMA - Suhendah, Rousilita; Patricia, Ivonne; Sylvia (Jurnal Serina Abdimas, 2024)
Accounting lessons for high school students in grades X-XII require high attention and concentration because each chapter in the accounting curriculum is interconnected. The high school accounting material is divided into sections for service companies and trading companies. In service companies, we will cover topics such as journal and ledger creation, trial balances, adjusting entries and adjusted trial balance, worksheets, and the production of financial reports. In the course of community service activities, the team will administer an initial test to assess the abilities of class X-XII students before training. Then, the community service team will provide material related to adjusting journals, using a problem-based solving method to create a trial balance after adjustments. This method is applied because the accounting material in secondary schools typically consists of concise, individual questions, which can present challenges for students to comprehend and work through. Following this, the team will conduct a post-test to evaluate the results of the students' abilities and understanding of the accounting material taught during the training. The average pre-test score was 46.67, and the post-test score was 71.11. This indicates that the accounting material training using the Problem-Based Solving method has led to an improvement in the students' understanding and abilities before and after the training. The Problem-Based Solving method employed by the PKM team demonstrates that the training participants, specifically the students in classes X-XII of Tarsisius 1 Catholic High School, have developed critical thinking skills and problem-solving abilities, thereby enhancing their understanding of the material covered in the training. ABSTRAK Pelajaran akuntansi bagi siswa-siswi SMA kelas X-XII merupakan pelajaran yang membutuhkan perhatian dan konsentrasi yang tinggi, karena di setiap bab materi pelajaran akuntansi saling berkaitan satu dengan yang lainnya. Pada materi akuntansi yang diajarkan di sekolah menengah ini terbagi menjadi akuntansi Perusahaan jasa dan Perusahaan dagang. Pada Perusahaan jasa akan dipelajari mulai dari pembuatan jurnal, buku besar, neraca saldo, jurnal penyesuaian, neraca saldo setelah disesuaikan, neraca lajur , dan dilanjutkan dengan pembuatan laporan keuangan. Pada saat pelaksanaan PKM, tim akan memulai dengan memberikan tes awal dengan tujuan agar tim PKM dapat mengetahui sejauh mana kemampuan siswa-siswi kelas X-XII sebelum dilakukan pelatihan. Tahap selanjutnya, Tim PKM memberikan materi yang berkaitan dengan jurnal penyesuaian sampai pembuatan neraca saldo setelah disesuaikan dengan metode problem based solving. Metode problem based solving ini diterapkan karena pada umumnya pemberian materi akuntansi di sekolah menengah merupakan materi singkat dan soal-soal yang bersifat individu sehingga siswa-siswi tidak paham dan mengalami kesulitan mengerjakan soal-soal akuntansi. Tahap berikutnya tim akan memberikan post test untuk melihat hasil kemampuan dan pemahaman siswa-siswi terhadap materi akuntansi yang sudah diajarkan oleh tim PKM. Rata-rata nilai pre-test sebesar 46,67 dan post-test sebesar 71,11. Ini berarti bahwa pada pelatihan materi akuntansi dengan metode Problem Based Solving menunjukkan adanya peningkatan pemahaman dan kemampuan siswa yang mengikuti pelatihan sebelum dan sesudah pelatihan. Metode Problem Based Solving yang diadopsi oleh tim PKM menunjukkan bahwa peserta pelatihan yaitu siswa kelas X-XII SMA Katolik Tarsisius 1 memiliki kemampuan berpikir kritis dan mempunyai keterampilan yang dapat memecahkan masalah serta menambah pemahaman pengetahuan akan materi yang dilatih